2013
DOI: 10.1166/jnn.2013.8199
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Electronic Structure of the Interfaces Between 2-TNATA and MoO<SUB><I>x</I></SUB>

Abstract: In order to understand the characteristics of ohmic hole-contacts for the inverted/conventional organic light emitting devices, a hole-only device with all ohmic contacts, which is composed of glass/ITO/MoOx/4,4,4-tris[2-naphthyl-phenyl-amino]triphenylamine (2-TNATA)/MoOx/Al, the elements of the electronic structures of MoOx-on-2-TNATA interface and 2-TNATA-on-MoOx interface were investigated by photoemission spectroscopy, with regards to interface energetics, formative mechanism, and a potential charge carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…One approach is to build an interface dipole moment oriented away from the cathode contact, pulling up the vacuum level of the cathode and lowering the electron injection barrier. 25,26 Wei et al demonstrated the successful application of evaporated ZnS lm as electron injection materials in uorescent and phosphorescent OLEDs to enhance electron injection and mitigate the operation voltage in inverted OLEDs. 27 However, the high-temperature deposited process limited its practical large-scale and low-coat applications.…”
Section: Introductionmentioning
confidence: 99%
“…One approach is to build an interface dipole moment oriented away from the cathode contact, pulling up the vacuum level of the cathode and lowering the electron injection barrier. 25,26 Wei et al demonstrated the successful application of evaporated ZnS lm as electron injection materials in uorescent and phosphorescent OLEDs to enhance electron injection and mitigate the operation voltage in inverted OLEDs. 27 However, the high-temperature deposited process limited its practical large-scale and low-coat applications.…”
Section: Introductionmentioning
confidence: 99%